2003
DOI: 10.1086/378177
|View full text |Cite
|
Sign up to set email alerts
|

Rotational Rest Frequencies for FeN ( X 2 i ) and Revised Spectroscopic Constants for FeC ( X 3 i )

Abstract: The pure rotational spectrum of FeN in its X 2 D i ground state has been recorded using millimeter-wave direct absorption techniques in the range 198-525 GHz. New measurements have also been carried out for FeC (X 3 D i ), in particular of the fine-structure component and the 54 FeC isotopomer. These molecules were created by Q p 1 the reaction of iron vapor with either CH 4 (FeC) or N 2 (FeN) in a DC discharge. Eight rotational transitions were recorded for FeN in its lowest-lying spin component, , and multip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 18 publications
2
11
0
Order By: Relevance
“…1). As found in the X 3 D state of FeC [18], the X = 2 line of TiS appears to be shifted to higher frequency relative to the other two components. This effect may be the result of the nearby isoconfigurational a 1 D state.…”
Section: Discussionsupporting
confidence: 56%
“…1). As found in the X 3 D state of FeC [18], the X = 2 line of TiS appears to be shifted to higher frequency relative to the other two components. This effect may be the result of the nearby isoconfigurational a 1 D state.…”
Section: Discussionsupporting
confidence: 56%
“…Searches for FeNC had been attempted by the Ziurys group using Broida oven synthesis methods, as employed for species such as FeC and FeN, 26 for several years prior to this work. Use of an ac discharge with Fe(CO) 5 proved to be a major factor in the success of the project.…”
Section: Resultsmentioning
confidence: 99%
“…The bond distance in CrC is comparable to that in NiC, which has r 0 = 1.6308 Å 16 -both of which are larger than those in FeC (1.5931 Å) and CoC (1.5612 Å). 15,16 CrC is thought to have an electron configuration of 8σ 2 3π 4 1δ 2 , with the 8σ and 3π orbitals creating a triple bond. 25 NiC is also thought to have a triple bond and an 8σ 2 9σ 2 3π 4 1δ 4 configuration, with the additional 4 electrons filling the non-bonding 1δ and 9σ orbitals.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12][13][14] Pure rotational data have been recorded for FeC, CoC, and NiC as well. 15,16 These studies have demonstrated that the ground states of these molecules are 3 ∆, 2 Σ + , 1 Σ + , 2 ∆, and 3 Σ + , respectively. For the metal monoacetylides, CuCCH and ZnCCH have been characterized using pure rotational spectroscopy, 17,18 and recently NiCCH and CuCCH have been studied in the optical regime.…”
Section: Introductionmentioning
confidence: 99%